Vision machine. - Ayrault, Jean-Marc; Bogner, Dieter; Brayer, Marie-Ange; Buci-Clucksmann, Christine; Chéroux, Clément; Cisbourne, Mark; Döhl, Reinhard; Fauchereau, Serge; Karnicka, Zenobia; Kiesler, Frederick; Kohso, Sabu; Lootsma, Bart; et al. (Paris : Somogy éditions d'art, 2000)
Archigram ; Barry, Judith ; Bloc, André ; Brauner, Victor ; Briand, Mathieu ; Chanéac ; Ciurlionis, Mikalojus Konstantinas ; Constant ; Darget, Louis ; Hartog, Jacci Den ; Pillard, Roger ; Durville, Gaston ; Emmerich, David-Georges ; Ernst, Max ; Finsterlin, Hermann ; Friedman, Yona ; Guébhard, Adrien ; Hausermann, Pascal ; Miller, Karol ; Coop Himmelb(l)au ; Hirschhorn, Thomas ; Hollein, Hans ; Höller, Carsten ; Bertin, Imbert & ; Kiesler, Frederick ; Klee, Paul ; Kupka, Frantisek ; Kurokawa, Kisho ; Lislegaard, Ann ; David, Emile ; Luys, Jules-Bernard ; Courtier, T. ; Majewski, Adrien ; Marey, Etienne-Jules ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Michaux, Henri ; Mikami, Seiko ; Morgner, Wilhelm ; Narkievicz-Jodko, Jacob von ; Parrent, Claude ; Pichler, Walter ; Polke, Sigmar ; Pollock, Jackson ; Ritchie, Matthew ; Rottier, Guy ; Schein, Ionel ; Solar, Xul ; Szekely, Pierre ; Tanguy, Yves ; Tosani, Patrick ; Atelier van Lieshout ; Vasulka, Steina & Woody ; Wallinger, Mark ; Witkacy ; Yvon, Paul
Vision machine, Musée des Beaux-Arts de Nantes, 13 mai - 10 septembre 2000
Frans
boek